Studi Analisis Hukum Pernikahan Adat Sunda Menurut Perspektif Islam - Bilqis Aprilia Salima; Dwi Putri Rahayu; Mentari Devi Nur Ramandini; Mohammad Rindu Fajar Islamy (Purwadita : Jurnal Agama dan Budaya, 2023)
Traditional Sundanese weddings have a series of procedures or traditions that must be carried out by the bride and groom and their families before the wedding day and on the wedding day. This activity is not just done, but has its own meaning and purpose which is useful for the lives of the two brides after marriage. So the purpose of this research is how Islamic law deals with things like that. The method used in this study is the interview method. Interviews were conducted online via Google Meet and offline or face to face. After being reviewed by researchers, there are several traditional Sundanese wedding processions that include their illegal laws because they have the potential to cause harm, are not in accordance with Islamic religious teachings and/or approach other religious rituals. The traditional procession in question is ngaras and siraman as well as ngeningan in pre-wedding customs, then the sawer Panganten custom for the Sabada Marriage custom